Impact of expressive intentions on upper-body kinematics in two expert pianists - Turner, Craig; Mailly, Robin; Dal Maso, Fabien; Verdugo, Felipe (Frontiers in Psychology, 2025)
IntroductionExpression is a key aspect of music performance. Studies on pianists’ gestures and expression have mainly documented the impact of their expressive intentions on proximal segments and head linear kinematics. It remains unclear how pianists’ expressive intentions influence joint angular kinematics as well as exposure to risk factors of injury, such as poor overall posture and distal jerky movements, two kinematic factors linked to injury. The first objective of this exploratory case study was to analyze the influence of pianists’ expressive intentions on proximal and distal joint range of motion (ROM) across different musical contexts. The second objective was to evaluate the impact of expressive intentions on the posture of joints that are commonly injured in pianists, as well as distal joint angular jerk. Methods: Two expert pianists (P1 and P2) performed six musical excerpts (E1–E6) in two experimental conditions: normal condition (including expressive intentions) and the control condition (strictly playing the composer’s notations written in the score with no subjective interpretation). An inertial measurement unit system recorded upper body kinematics.MethodsTwo expert pianists (P1 and P2) performed six musical excerpts (E1–E6) in two experimental conditions: normal condition (including expressive intentions) and the control condition (strictly playing the composer’s notations written in the score with no subjective interpretation). An inertial measurement unit system recorded upper body kinematics.Results and discussionBoth proximal and distal joint ROM increased when pianists incorporated expressive intentions. Participants exhibited more static, non-neutral wrist postures when incorporating expressive intentions (right and left wrist for P1 and P2, respectively), suggesting an increased risk of distal injury. On the contrary, the thorax exhibited more dynamic, neutral flexion postures, suggesting a reduced risk of proximal injury. These results suggest that expressive intentions may impact proximal and distal postures differently. Incorporating expressive intentions also led to jerkier, less smooth wrist movements in lyrical, non-virtuosic musical excerpts (E1–E4). However, in more virtuosic excerpts (E5–E6), there were generally no differences between conditions. Spatiotemporal constraints might explain these discrepancies between non-virtuosic and virtuosic musical excerpts. These results provide evidence of the impact of expressive intentions on the entire kinematic chain, while highlighting the implications of the subjective dimension of music expression in relation to exposure to risk factors of injury.